Education in the Era of IR 4.0 - Hasnah, Haron (2018)
IR 4.0 also known as the ‘digital revolution’: combines technological and human capacities in an unprecedented way through self- learning algorithms, self-driving cars, human–machine interconnection and big-data analytics.